Development of Snack Bar (Snack Bar) In Rich In Calcium With Fortification Of Shell Flour Kijing (Anadonta Woodiana) - Fatmi, Mindiya; Rustiani, Erni (Journal of Science Innovare, 2018)
Shellfish flour has a proximate content including moisture content, ash content, fat content, protein content and calcium levels. Shellfish flour containing rich calcium can be added in the manufacture of food products such as Snack Bar to increase the nutritional value. The research includes making snack bar barbecue with several types of sweeteners such as honey, palm sugar and sorbitol. Based on the results of proximate and minerals test, it was found that snack bar preparations were made with ash content (2.25, 2.04, 1.88), total fat content (20,34,20,75,24,20) and kalisum (823,78; 506,21; 814,06) which is higher than the positive control. lower protein and phosphorus content than positive controls, and total carbohydrates that approach positive controls. Keywords: Shellfish Flour, Snack-Bar, Sweetener, Proximate Tes